Smart material optimization using reinforcement learning in multi-dimensional self-assembly - Zou, Yiming (Frontiers in Materials, 2025)
IntroductionIn recent years the design and optimization of smart materials have gained considerable attention due to their potential applications across diverse fields, from biomedical engineering to adaptive structural systems. Traditional approaches for optimizing these materials often rely on deterministic models ortrial-and-error processes, which tend to be limited by computational expense and lack of adaptability in dynamic environments. These methods generally fail to address the complexities of multi-dimensional self-assembly processes where materials need to respond autonomously to environmental stimuli in real time.MethodsTo address these limitations, this research explores the application of reinforcement learning (RL) as an advanced optimization framework to enhance the autonomous self-assembly of smart materials. We propose a novel reinforcement learning-based model that integrates adaptive control mechanisms within multi-dimensional self-assembly, allowing materials to optimize their configuration and properties according to external stimuli. In our approach, agents learn optimal assembly policies through iterative interactions with simulated environments, enabling the smart material to evolve and respond to complex and multi-factorial inputs.Results and discussionExperimental results demonstrate the model’s efficacy, revealing significant improvements in adaptability, efficiency, and material performance under varied environmental conditions. The work not only advances the theoretical understanding of self-assembly in smart materials but also paves the way for the development of autonomous, self-optimizing materials that can be deployed in real-world applications requiring dynamic adaptation and robustness.